Project communication management in complex environments - Ying, Zhong; Sui Pheng, Low (Springer Singapore Imprint: Springer, 2014)
This unique book that deals with project communication management in complex environments, taking a leaf from China's experience with a major earthquake in Sichuan, would be a timely contribution to fill this lacuna. Readers would be able to understand how companies and organizations that are unprepared for crisis management would react to their detriment. The lessons provided in this book are the only one of its kind to highlight the lessons for companies and organizations to prepare themselves for successful project communication management through the complexity-informed framework. Although the book is written by two building professionals, the concepts and lessons presented are generic and equally applicable for businesses outside of the construction industry; for example, for airports, resorts, hotels, shipyards, etc.